2019
DOI: 10.33594/000000159
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac Inflammation after Ischemia-Reperfusion of the Kidney: Role of the Sympathetic Nervous System and the Renin-Angiotensin System

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…Excessive inflammation injury induces cardiomyocyte dysfunction through various mechanisms including, but not limited to, the induction of cardiomyocyte apoptosis, promotion of intracellular energy depletion, stimulation of cardiomyocyte oxidative stress, and disruption of myocardial microcirculation (Lee et al, 2018;Ronco et al, 2018;Di Lullo et al, 2019). IL-6 has been reported to be an important mediator of cardiac inflammation after AKI (Panico et al, 2019), although the pathological role of IL-6 in cardiac dysfunction following AKI has not been fully understood. In the present study, our data showed that increased IL-6 induced an upregulation of Grb2, resulting into the impairment of mitochondrial bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive inflammation injury induces cardiomyocyte dysfunction through various mechanisms including, but not limited to, the induction of cardiomyocyte apoptosis, promotion of intracellular energy depletion, stimulation of cardiomyocyte oxidative stress, and disruption of myocardial microcirculation (Lee et al, 2018;Ronco et al, 2018;Di Lullo et al, 2019). IL-6 has been reported to be an important mediator of cardiac inflammation after AKI (Panico et al, 2019), although the pathological role of IL-6 in cardiac dysfunction following AKI has not been fully understood. In the present study, our data showed that increased IL-6 induced an upregulation of Grb2, resulting into the impairment of mitochondrial bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, while no strong changes in renal AT1R expression were observed in enalapril-treated mice, part of the reduction in renal inflammation and damage can also be due to the expected reduction of AngII peptide, since enalapril is a strong ACE inhibitor. AngII has been associated to kidney inflammation in several models (Theuer et al, 2002;Altunoluk et al, 2006;Benigni et al, 2011;Nagasawa et al, 2012;Kanda et al, 2016;Ham et al, 2018;Panico et al, 2019), and the FIGURE 7 | Carboxypeptidase M mRNA expression in renal tissue and mouse epithelial tubular cells. The panels show CPM mRNA expression (A) in mice 24 h after treatment with cisplatin or cisplatin plus enalapril and CPM mRNA expression (B) in mouse tubular cells after treatment with cisplatin or enalaprilat plus cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that ACE influences the regulation of both kinin receptors in vascular smooth muscle cells (Ignjacev-Lazich et al, 2005). Moreover, it has already been shown that ACE inhibition protects against some types of renal disease (Ghosh et al, 2009(Ghosh et al, , 2012Vejakama et al, 2012;Ding et al, 2014;Ham et al, 2018;Panico et al, 2019), including cisplatin-induced kidney disfunction (El-Sayed el et al, 2008), but only renal function and reactive oxygen species were assessed in this work. Given that (a) inflammation has an important role in cisplatin nephrotoxicity; (b) AngII influences the regulation of inflammation-related genes; and (c) ACE inhibition reduces kinin degradation, we decided to verify whether the protective effect of ACE inhibition on the attenuation of cisplatin nephrotoxicity is related to KKS regulation.…”
Section: Introductionmentioning
confidence: 90%
“…It is well known that not all cytokines are involved at all stages of inflammation, but some of them do mediate both acute and chronic responses. This is the case of TNF-α, IL-1 (α and β) and IL-6 [ 229 ], which are some of the most studied ones and have been suggested to have an important role in inflammatory modulation during CRS due to its extremely potent proinflammatory effects [ 94 , 230 , 231 , 232 ].…”
Section: Mechanisms Involved In Fibrosis Progressionmentioning
confidence: 99%